Penggunaan Limbah Beton Sebagai Agregat Pada Campuran Stone Matrix Asphalt Halus - Grace; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2021)
Concrete waste in Indonesia in general has not been used properly and is left without any handling which will cause its own problems for the environment, therefore it needs processing so that it can be used as a more useful material. This study aims to determine the characteristics of the concrete waste to be used in the Stone Matrix Asphalt mixture, determine the composition of the Stone Matrix Asphalt mixture using concrete waste and determine the ability of the mixture to influence temperature and water after immersion. The research methodology uses the Conventional Marshall method to obtain the characteristics of the waste concrete used in the mixture of Stone Matrix Asphalt and Marshall Immersion to obtain the Marshall Residual stability value. The results showed that the aggregate characteristics of the waste concrete met the requirements for the mixture of road pavements. Based on the mixed composition design, the composition of the mixture obtained for asphalt content is 6.00%, coarse aggregate is 69.50%, fine aggregate is 16.00%, and filler is 8.50. The use of a mixture of Stone Matrix Asphalt Smooth through testing Characteristics of the Conventional Marshall mixture obtained Stability, Meltability (flow), Void In Mix (VIM), Void In Mix Aggregate (VMA) values, meet the specifications, Marshall Immersion test results obtained an immersion index of or Residual Strength 92.02% means that the mixture is resistant to the duration of immersion.